OQÍW SABAQLARÍNDA BASLAWÍSh KLASS OQÍWShÍLARÍNÍŃ TARIYXÍY SANASÍN QÁLIPLESTIRIW - Tulepbergenova, B.B. (SCIENCE and SOCIETY, 2023)
The content, theoretical foundations, and analysis of the concepts aimed at the formation of historical consciousness are mentioned in the article. In the process of education, the development stages of the formation of students’ historical thinking and ideas about historical consciousness are presented.